Effects of Early Motor Interventions on Gross Motor and Locomotor Development for Infants at-Risk of Motor Delay: A Systematic Review - Dumuids-Vernet, Marie-Victorine; Provasi, Joëlle; Anderson, David Ian; Barbu-Roth, Marianne (Frontiers in Pediatrics, 2022)
AIM: To systematically examine the effect of early motor interventions on motor and locomotor development in infants less than one year of age with motor developmental disability or at risk of motor delay. METHOD: Pertinent literature from January 2000 to September 2021 was identified by searching the PubMed, Embase, Cochrane, Pedro and Web of Science databases. Selection criteria included interventions starting before 12 months corrected age. Methodological quality was assessed with AACPDM criteria, Mallen score and Cochrane risk of bias methodology. Evaluation procedure was performed using PRISMA protocol (PICO approach) and AMSTAR-2. This review was preregistered in PROSPERO (CRD42021286445). RESULTS: Ten articles met the inclusion criteria; seven had moderate to strong methodological quality. The interventions included treadmill training (n=3), crawling training (n=1), “tummy time” (n=1), physical therapy with neonatal developmental program (n=1) or Bobath approach (n=1), treadmill training combined with active leg movements (n=2) or Bobath physiotherapy (n=1). The three key characteristics of effective interventions that emerged from the review were: (1) the infants’ disability or risk of delay was well defined; (2) the protocol was standardized and easy to replicate; (3) infants were required to make active movements. CONCLUSION: There is an urgent need for additional high-quality studies on the effects of early motor interventions on the gross motor and locomotor development of infants with a range of disabilities or risks for delay. Suggestions for future research are outlined. “What this paper adds” • Few early motor intervention studies exist. • The majority of selected studies have moderate to strong methodological quality. • Interventions were more effective when infants’ disability or delay risk was well-defined. • Interventions were more effective when the protocol was standardized. • Interventions were more effective when infants were required to make active movements. Shortened form of the title: Early motor interventions